Removal of Cr(VI) from Aqueous Solution by Baritite Clay Adsorption - Peng, Ge; Liu, Wangcai; Li, Qiuping; Zhang, Haojian; Huang, Hui (Asian Journal of Chemistry, 2014)
Among the investigated clays and minerals (kaolinite, natural zeolite, manual zeolite, bentonite, sepiolite, sepiolite amianthus, tremolite amianthus, vermiculite and baritite), the baritite clay was selected as the optimal adsorbent for aqueous Cr(VI). The adsorption capacity of Cr(VI) on baritite clay reached as high as 39.01 mg g-1 at 20 °C. Then the adsorption kinetics and thermodynamics of Cr(VI) by the baritite clay were studied. Results showed that the pseudo-second-order model was a suitable description for the adsorption kinetics and fitted well with the experimental data. The calculated values of entropy (DS°) and enthalpy (DH°) changes of the adsorption process were DH° = -9.653 kJ/mol and DS° = -22.57 J mol-1 K-1. This indicated that the adsorption of Cr(VI) on baritite clay was an exothermic process with chemical reactions. Finally, a hypothetical chemical adsorption mechanism of Cr(VI) was proposed.